miRNA-21 as a novel therapeutic target in lung cancer - Markou A; Zavridou M; Lianidou ES (Lung Cancer: Targets and Therapy, 2016)
Athina Markou, Martha Zavridou, Evi S LianidouAnalysis of Circulating Tumor Cells, Laboratory of Analytical Chemistry, Department of Chemistry, University of Athens, Athens, GreeceAbstract: Lung cancer is a leading cause of cancer death, and late diagnosis is one of the most important reasons for the high mortality rate. microRNAs (miRNAs) are key players in gene regulation and therefore in tumorigenesis. As far as lung carcinogenesis is concerned, miRNAs open novel fields in biomarker research, in diagnosis, and in therapy. In this review we focus on miR-21 in lung cancer and especially on how miR-21 is involved 1) as a biomarker in response or resistance to therapy or 2) as a therapeutic target.Keywords: lung cancer, miR-21, therapeutic target, NSCLC, response to therapy